Population pharmacokinetics of tenofovir, emtricitabine and intracellular metabolites in transgender women. Issue 8 (25th March 2022) - Tanaudommongkon, Asama; Chaturvedula, Ayyappa; Hendrix, Craig W.; Fuchs, Edward J.; Shieh, Eugenie; Bakshi, Rahul P.; Marzinke, Mark A.
Abstract : Aims: Transgender women (TGW) have been underrepresented in trials and use gender‐affirming hormonal therapies (GAHT) that may alter renal function by significantly increasing creatinine clearance. Population pharmacokinetic (popPK) models and simulations would aid in understanding potential differences in emtricitabine/tenofovir disproxil fumarate (F/TDF) parent–metabolite concentrations in TGW on GAHT when compared to cisgender men (CGM) not exposed to GAHT. Methods: Pharmacokinetic (PK) data from a Phase 1, open‐label clinical trial with directly observed therapy of daily F/TDF consisting of 8 TGW and 8 CGM was utilized for model building. PopPK analysis was performed using nonlinear mixed effects modelling (NONMEM 7.5.0). Covariates of body weight, creatinine clearance, and gender were evaluated. Final models were subjected to Monte Carlo simulations to compare drug exposure following once daily and on‐demand (IPERGAY 2 + 1 + 1) dosing of F/TDF. Results: Tenofovir (TFV) and emtricitabine PK were best described by a 2‐compartment model, first‐order absorption/elimination with absorption lag time. Parent models were linked to their metabolites by first order formation and elimination. Creatinine clearance was a significant covariate influencing clearance in both models. Simulations demonstrated that at least 2, weekly 2 + 1 + 1 cycles of on‐demand dosing in TGW on GAHT is necessary for TFV‐diphosphate to reach similar exposure after the initial week of on‐demand dosing in CGM not on GAHT. Conclusion: PopPK models of TFV, emtricitabine and intracellular metabolites in TGW were established. Dose simulations revealed that TGW should be treated for at least 2 weeks to have comparable exposures to CGM.